The Effects of Electricity Consumption on Agriculture, Service and Manufacturing Sectors in Malaysia - Pei, Tan Lee; Shaari, Mohd Shahidan; Tunku Ahmad, Tunku Salha (International Journal of Energy Economics and Policy, 2016)
This paper aims to examine the effects of electric consumption on three sectors, namely, manufacturing, agriculture and services. The Johansen co-integration model is applied. The results indicate a long-run relationship between electric consumption and three sectors in Malaysia. VECM shows that it is confirmed that the long run relationship among electric consumption, agriculture and manufacturing in Malaysia. The Granger causality is used, and the results show that electric consumption does not Granger cause manufacturing and services sectors. However electricity consumption does Granger cause agriculture sector. Keywords: Electricity consumption, Agriculture, Service, Manufacturing JEL Classifications: Q11, Q43